Stakeholder acceptance and attitudes toward dengue prevention: A study on fogging and autocidal traps techniques in Malaysia - Noor Sharizad Rusly; Nur Asmadayana Hasim; Ahmad Firdhaus Arham; Latifah Amin (PLoS ONE, 2025)
The ineffectiveness of current prevention efforts is underscored by the increasing number of dengue cases, emphasizing the necessity of innovative approaches. This investigation investigates the extent of stakeholder acceptability and attitudes toward the alternative autocidal trap method and the current fogging technique. The objective is to identify differences in community viewpoints regarding these control techniques among various stakeholder groups, including scientists and the public. Information was collected from two separate groups of individuals: scientists and the general people. A comprehensive survey assessed the level of tolerance and attitudes towards fogging and autocidal traps. Statistical analysis was performed using the SPSS software, specifically utilizing the one-way MANOVA test, to identify any significant variations in attitudes among various stakeholder groups. The results reveal significant discrepancies in the perceived danger level between the two groups since the public views fogging as a riskier activity than scientists. However, the groups had no significant difference in the reported benefits. Scientists exhibited a greater degree of endorsement for both fogging and autocidal traps when compared to the public. While the general population showed more openness towards fogging, scientists have shown a more balanced approval of both tactics. These insights are essential for policymakers and health practitioners as they inform the creation of more efficient, community-oriented initiatives to address the increasing prevalence of dengue cases.